Emission and dispersion of gaseous pollution from exhaust shafts of copper mine = Emisja i dyspersja zanieczyszczeń gazowych z szybów wydechowych kopalni miedzi - Jasiewicz, Marzena; Słobodzian-Ksenicz, Oryna; Gromadecka, Sylwia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The primary objective of the study was to determine the volumes of emission and dispersion of gaseous pollution from 3 exhaust shafts of a copper mine P-VII, SW-3 and SG-2. To calculate the volumes of emission and dispersion of SO2, NO2and CO the KOMIN and RWW computer programs were applied.
Keywords: kopalnia miedzi; szyby wydechowe; zanieczyszczenia gazowe; emisja; dyspersja; exhaust shafts; gaseous pollution; emissions; dispersion